2003
DOI: 10.1016/s0920-5632(03)01533-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the quark propagator

Abstract: The quark propagator is at the core of lattice hadron spectrum calculations as well as studies in other nonperturbative schemes. We investigate the quark propagator with an improved staggered action (Asqtad) and an improved gluon action, which provides good quality data down to small quark masses. This is used to construct ansätze suitable for model hadron calculations as well as adding to our intuitive understanding of QCD. The lattice quark propagatorThe quark propagator is a fundamental quantity of QCD. Tho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
0
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 8 publications
7
89
0
1
Order By: Relevance
“…These predictions for the quark mass function have been confirmed in lattice simulations of QCD [14,15,16]. Pointwise agreement for a range of quark masses requires this interaction to be flavor-dependent [9], suggesting that dressing the quark-gluon vertex Γ i ν (q, p) is important.…”
Section: Quark Propagatormentioning
confidence: 72%
See 1 more Smart Citation
“…These predictions for the quark mass function have been confirmed in lattice simulations of QCD [14,15,16]. Pointwise agreement for a range of quark masses requires this interaction to be flavor-dependent [9], suggesting that dressing the quark-gluon vertex Γ i ν (q, p) is important.…”
Section: Quark Propagatormentioning
confidence: 72%
“…Dynamical quark mass functions obtained with the DSE-Lat model together with the quenched lattice data [15]. Adapted from [9].…”
Section: Lattice-inspired Rainbow Modelmentioning
confidence: 99%
“…The model parameter C for the vertex is determined by a fit to selected global features of quenched lattice-QCD data for the quark propagator [29] and the quark-gluon vertex [22]. Thess data are available for both quantities at current quark mass m =m = 60 MeV.…”
Section: B Algebraic Vertex and Quark Propagatormentioning
confidence: 99%
“…For example, DCSB is responsible for the generation of large constituent-like masses for dressedquarks in QCD, an outcome that could have been anticipated from Refs. [1,2]; it is a longstanding prediction of Dyson-Schwinger equation (DSE) studies [3] and has recently been observed in numerical simulations of latticeregularised QCD [4,5]. DCSB is also the keystone in the realisation of Goldstone's theorem through pseudoscalar mesons in QCD [6], and thereby the remarkably small value of the ratio of π-and ρ-meson masses, and the weak ππ interaction at low energies [7].…”
Section: Introductionmentioning
confidence: 99%